Radical cystectomy in the elderly â Is this a safe treatment option? - Matthew J. Young (Taylor & Francis Group, 2017)
Objective: To determine if significant differences exist in the perioperative outcomes of patients aged >75Â years treated with radical cystectomy (RC) compared to younger patients, as RC is frequently not offered to âelderlyâ patients with bladder cancer because of supposed increased risks of complications. Patients and methods: We retrospectively analysed prospectively collected data of all patients that underwent RC in our centre from May 2013 to June 2015. In all, 81 consecutive RCs were identified and included in our study. Patients were divided into two age groups: Group A, aged <75Â years (51 patients) and Group B, aged â¥75Â years (30). Co-morbidities and perioperative outcomes were compared between the groups. Fisherâs exact test was used for statistical analysis. Results: In 68 patients RC was performed laparoscopically and the remaining 13 patients underwent open RC. The mean (range) age was 70.7 (36â85)Â years. There were 37 patients with muscle-invasive disease and 42 had non-muscle-invasive disease. The median hospital stay was not significantly different between the two age groups (10 vs 11Â days). There was no significant difference in the preoperative Charlson co-morbidity index. The 30-day mortality rate was 4% for those aged <75Â years and 6.6% for those aged â¥75Â years, with overall perioperative complication rates of 57% vs 66%, respectively. Most complications were minor (ClavienâDindo Grade IâII) and there was no statistically significant difference between the two cohorts. There was also no statistically significant difference in blood transfusion rates. Conclusion: RC in patients aged â¥75Â years has similar perioperative morbidity when compared with younger patients and can be offered in selected elderly patients. Thus, age should not be an absolute contraindication for RC. Keywords: Bladder cancer, Elderly, Cystectomy, Minimally invasive, Laparoscopy